2010
DOI: 10.1007/s00894-010-0844-z
|View full text |Cite
|
Sign up to set email alerts
|

Sigma- and pi- electron structure of aza-azoles

Abstract: The reasons behind changes of aromaticity in 10 unsubstituted aza-azoles was analysed by employing the Natural Bond Orbital (NBO) approach at the MP2/6-311+G(d,p) level of theory. Sum of occupations of p z orbitals at atoms in the ring correlates well with the magnetism based aromaticity index NICS as well as with the number of nitrogen atoms in the ring. Changes of NICS depend strongly in a linear way on the number of NN bonds.Classification of azoles based on the number of pyridine-type nitrogen atoms vicina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Correlation between pEDA and NICS has previously been recognised in a study of aza-azoles. 52 The rings 8e9 are slightly p rich and the calculated pEDA values (Table 1) are consistent with rings associated with 6.3AE0.1 p electrons. This contrasts with our earlier study of six-membered isomers, 2 which are much more electron rich (pEDA 7.0AE0.2), and accordingly display lower magnetic aromaticity as measured by the NICS index.…”
Section: Resultssupporting
confidence: 77%
“…Correlation between pEDA and NICS has previously been recognised in a study of aza-azoles. 52 The rings 8e9 are slightly p rich and the calculated pEDA values (Table 1) are consistent with rings associated with 6.3AE0.1 p electrons. This contrasts with our earlier study of six-membered isomers, 2 which are much more electron rich (pEDA 7.0AE0.2), and accordingly display lower magnetic aromaticity as measured by the NICS index.…”
Section: Resultssupporting
confidence: 77%
“…Using quantum chemical approaches, many efforts have been made to model the substituent effect . Substituent effects are responsible for small perturbations on the molecular electron density distribution, which can be measured by means of correlating them with the computed quantities of total energy, atomic charges, and electrostatic potentials resulting from ab initio quantum chemical or semiempirical methods . Further, several experimental studies have utilized Y‐G‐X type systems to understand the substituent effect transmission ability of various spacer moieties using geometrical variables, ionization techniques, and NMR chemical shifts etc …”
Section: Introductionmentioning
confidence: 99%
“…One more quantitative characteristic based on quantum chemistry modeling is charge of the substituent active region, with an acronym cSAR(X), which is a sum of atomic charges of all atoms of the substituent X and the carbon atom to which the X is attached. Recently, it has been shown that cSAR(X) values correlate well with SCs . Very important feature of cSAR(X) characteristic is its independence of the method of the atomic charge assessment; the obtained by different methods quantities exhibits good mutual correlations …”
Section: Introductionmentioning
confidence: 99%